Efektivitas Deep Breathing Exercise terhadap tingkat Stress pada Lansia - Devina Puspa Wulandari; Laksmita Dewi Adzillina (Universitas Muhammadiyah Manado, 2024)
Stress in the elderly is a health problem that can affect their quality of life and physical and mental health. This study aims to determine the effect of breathing exercise on reducing stress levels in the elderly. The research design used was quasi-experimental with pre-test and post-test in the experimental group. A total of 32 elderly people were given regular breathing exercises for 4 weeks. Measuring tools used to assess PSS stress levels. The results of the analysis showed a significant decrease in stress levels, namely from 21.90 to 20.190 (p<0.001). Thus, breathing exercises have proven to be effective in reducing stress levels in the elderly. This research suggests applying breathing exercises as a non-pharmacological approach to managing stress in the elderly.